Analisis Perbandingan Model Altman dan Model Springate untuk Memprediksi Kesehatan Keuangan Perusahaan pada PT Garuda Indonesia Tbk Periode 2020-2024 - Putri Amelia Sartika; Muhammad Yusuf; Fernando Africano (Indonesian Journal Publisher, 2026)
The purpose of this study is to analyze the comparison between the prediction of financial distress in PT Garuda Indonesia (Persero) Tbk using the Altman Z-Score model and Springate model in the years of 2020-2024. The reason for conducting the study is due to the company’s financial condition that has undergone dramatic changes due to the COVID-19 pandemic, PKPU proceedings, and debt restructuring. In this study, the qualitative descriptive method was used with the secondary data that was taken from annual financial statements from Indonesia Stock Exchange using the purposive sampling method. From the research result, it is known that the Altman Z-Score. Model classified the company as being in financial distress in 2020, 2021, 2023, and 2024, and in the grey area in 2022. The Springate Model classified the company as potentially bankrupt in 2020, 2021, 2023, and 2024, and as healthy in 2022. Both models showed consistent results in four years of observation, but differed in 2022. The difference is due to the different weights of the variables, where Altman emphasizes solvency aspects more, while Springate is more sensitive to operational profitability. Overall, PT Garuda Indonesia's financial condition during the research period has not shown consistent stability.